2010
DOI: 10.1093/eurpub/ckq144
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency anaemia prevalence in a population of immigrated women in Italy

Abstract: The observed prevalence of sideropenia and sideropenic anaemia is much greater than what the scientific literature reports for Western populations. Pathologies inducing bleeding and the country of origin (i.e. genetic factors, pre-existing conditions) appear to be associated with anaemia. Nutritional factors are less important because of an adequate nutritional income. Prevention programmes should then aim at screening larger samples for improving the access of migrants to health-care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 9 publications
1
21
0
4
Order By: Relevance
“…We also documented a significant positive correlation between maternal Hb and low birth weight which is in line with previous studies [33] [34]. On the other side other studies failed to find such relationship [35] [36] [37] [38].…”
Section: Discussionsupporting
confidence: 92%
“…We also documented a significant positive correlation between maternal Hb and low birth weight which is in line with previous studies [33] [34]. On the other side other studies failed to find such relationship [35] [36] [37] [38].…”
Section: Discussionsupporting
confidence: 92%
“…Then, we combined studies using a random effects model and no significant relationship was observed between maternal anemia in the third trimester of pregnancy and LBW (relative risk, 1.21 [95% CI: 0.84 to 1.76] (9, 10, 16, 20, 29-32). Yildiz’s study had the highest weight (31).…”
Section: Resultsmentioning
confidence: 99%
“…Different studies with different values of relative risk and confidence interval were previously conducted (8-11, 16, 18-20, 22-24, 28-33). Various maternal criteria such as anemia, age, intervals between pregnancies, physical tumor factor and weight loss were included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We found no other studies in the literature comparing the iron status of preschool-aged immigrants with non-immigrants and only one study suggesting American Hispanic children has worse iron status compared with white non-Hispanic children 9. Studies on pregnant women suggest immigrant women have higher rates of ID compared with native-born women 36 37…”
Section: Discussionmentioning
confidence: 74%